Skin necrosis after SUPERknee procedure – typical versus modified surgical approach - Shadi, Milud; Janusz, Piotr; Koczewski, Paweł; Walczak, Michał; Kraśny, Joanna; Kotwicki, Tomasz (Journal of Medical Science, 2019)
Introduction. SUPERknee procedure (SK) is a treatment for complex knee instability in children with congenital deformations. Due to wide surgical approach and long time of surgery (ST) the skin around the knee is in risk of ischemic necrosis (SN) or healing complications (HC). Aim. The purpose of the study is to compare incidence of SN in SK using typical and modified approach.Material and Methods. Sixteen patients underwent SK since 2015 till 2016, in mean age 8.1 (4.3–12.7) y.o. In 8 cases SK and in 8 SK combined with SUPERhip (SK+SH) was performed. In 6 patients (3 SK and 3 SK+SH) the approach was performed from one incision (OIA). In 10 patients (5 SK and 5 SK+SH) a modified approach was performed, involving additional skin incision (DIA). The occurrence of SN, ST and risk factors of HC were evaluated. Results. SN appeared in 2 cases treated with OIA (33%). There was no SN in DIA (0%). With this number of patients the difference was below level of significance, p = 0.1250, OR = 11.7. In one patient treated with SK+SH area of SN was 17.5 cm2. In the other patient treated with SK 35 cm2. Mean ST in SK was 3.4h (2.5–4.0) and in SK+SH 4.6h (4.0–5.5). ST of the surgery with OIA was 4.1h (2.5–5.5) and in DIA 3.7h (3.0–4.5), p = 0.4746. No additional risk factor relevant to SN was found.Keywords: SUPERknee, SUPERhip, super knee, super hip, healing complications, skin necrosis.
Keywords: SUPERknee; SUPERhip; super knee; super hip healing complications; skin necrosis